Modulation of P-glycoprotein by Stemona alkaloids in human multidrug resistance leukemic cells and structural relationships - Sonthaya Umsumarng (2018)
© 2017 Elsevier GmbH Background Multidrug resistance (MDR) is a major reason for the failure of chemotherapy in the treatment of cancer patients. P-gp over-expression in MDR cancer cells is a multifactorial phenomenon with biochemical resistance mechanisms. Stemofoline (STF), isolated from Stemona bukillii, has been reported to be an MDR reversing compound. Purpose This study investigated whether other Stemona alkaloids that had been purified from Stemonaceae plants exerted MDR modulation activity. Methods MTT assay was performed to determine the MDR reversing property of the alkaloids. Modulation of P-gp function by these compounds was investigated using cell cycle analysis and P-gp fluorescent substrate accumulation assays. P-gp expression was determined by Western blot analysis. We preliminarily examined the safety of these compounds in normal human fibroblasts and human peripheral blood mononuclear cells (PBMCs) using the MTT assay, and in red blood cells (human and rat) through in vitro hemolysis assays. Results Three of the eight alkaloids tested, isostemofoline (ISTF), 11Z -didehydrostemofoline (11Z-DSTF) and 11E-didehydrostemofoline (11E-DSTF), enhanced the chemotherapeutic sensitivity of MDR leukemic K562/Adr cells, which overexpressed P-gp. The P-gp functional studies showed that these three alkaloids increased the accumulation of P-gp substrates, calcein-AM (C-AM) and rhodamine123 (Rho 123) in K562/Adr cells, while this effect was not seen in drug sensitive parental K562 cells. Whereas, the alkaloids did not alter P-gp expression as was determined by Western blotting analysis. Conclusion The alkaloids reversed MDR via the inhibition of P-gp function. For pharmaceutical safety testing, the alkaloids were found to be not toxic to normal human fibroblasts and PBMCs. Moreover, the effective compounds did not induce hemolysis in either human or rat erythrocytes. These compounds may be introduced as potential candidate molecules for treating cancers exhibiting P-gp-mediated MDR.